Обмеження доступності вищої освіти як спосіб підняття її конкурентноспроможності - Пічієнко, М. Г. (ХНУРЕ, 2020)
Ukrainian education system has appeared to be uncompetitive on the еuropean market. Most universities have a lack of governmental funding, they are applied by entrants with low IET (External independent testing), and their diplomas are not valued among employers. This situation needs to bechanged. We should reconsider our opinion about the importance of the high education фand promote its reformation.
Keywords: філософія; обмеження доступності вищої